Design, analysis and fabrication of desk mount laptop stand with cooler / Anaqi Bunyamin Zulhazmi and Ahmad Faidzal Khodori - Zulhazmi, Anaqi Bunyamin; Khodori, Ahmad Faidzal (School of Mechanical Engineering, 2022)
Mechanical Engineering students of semester 4 were given a task to create a product that helps in solving everyday problems. An idea to solve a common problem for laptop users is used for this project which are overheating and the lack of workspace. The objective of this project is to design a laptop stand that helps in increasing the cooling performance of the laptop and gives the user more workspace to be utilised. This proposal contains the major steps in manufacturing a product which are doing research, literature review, implementing a concept design to be visualised in a 3D rendering software, and fabrication. The knowledge that has been learned throughout the Mechanical Engineering courses will be fully utilised in this project. Upon the completion of this project, a more in-depth understanding will be gained and improvement in the ability to write a solid proposal for fabricating an engineering design will assist the students in the future professional environment of the engineering world.